Human immune disorder arising from mutation of the α chain of the interleukin-2 receptor - Sharfe, Nigel (The National Academy of Sciences of the USA, 1997)
Profound cellular immunodeficiency occurs as the result of mutations in proteins involved in both the differentiation and function of mature lymphoid cells. We describe here a novel human immune aberration arising from a truncation mutation of the interleukin-2 receptor α chain (CD25), a subunit of the tripartite high-affinity receptor for interleukin 2. This immunodeficiency is characterized by decreased numbers of peripheral T cells displaying abnormal proliferation but normal B cell development. Extensive lymphocytic infiltration of tissues, including lung, liver, gut, and bone, is observed, accompanied by tissue atrophy and inflammation. Although mature T cells are present, the absence of CD25 does affect the differentiation of thymocytes. While displaying normal development of CD2, CD3, CD4, and CD8 expression, CD25-deficient cortical thymocytes do not express CD1, and furthermore they fail to normally down-regulate levels of the anti-apoptotic protein bcl-2.